Legal Certainty and Procedural Justice in Land Management in Indonesia: Ensuring Rights Protection and Effective Dispute Resolution - Yuniar Sabdaningtyas; Putri Maha Dewi (Mimbar Keadilan, 2024)
Land disputes are a persistent issue in many countries, including Indonesia, often complicated by conflicting land certificates and ambiguous regulations. This article explores the multifaceted aspects of resolving such disputes, emphasizing the pivotal role of land certificates in achieving legal certainty. In addressing these challenges, the research employs the juridical-normative legal method to analyze the complexities inherent in land dispute resolution. A significant finding is that disputes involving dual certificates frequently entail multiple stakeholders, necessitating a meticulous determination of rights and liabilities among the parties involved. Thus, the principle of dignified justice becomes paramount in adjudicating these disputes, ensuring equitable outcomes for all parties. The prevalence of dual certificates exacerbates legal uncertainty for landholders, undermining the efficacy of certificates as conclusive evidence of ownership. Consequently, there is a pressing need for legislative reforms aimed at fortifying the validity and indisputability of land certificates. Strengthening the legal framework is essential to uphold the integrity of property rights and enhance confidence in the judicial process. Agrarian reform emerges as a pivotal strategy in addressing these issues, offering a systematic approach to resolve disputes and establish robust legal frameworks. By reforming existing regulations, stakeholders can mitigate ambiguities and streamline processes, thereby fostering an environment conducive to sustainable development and equitable land distribution. Effective resolution of land disputes hinges upon collaborative efforts among diverse stakeholders, including government bodies, legal institutions, and community representatives. These collaborations are instrumental in devising comprehensive strategies that promote legal certainty and uphold justice.